Implantação da energia fotovoltaica em um condomínio Residencial vertical - SANTOS, Amanda Pires dos (2021)
Photovoltaic solar energy is that which results from the photovoltaic effect, in which an electrical voltage is generated in a semiconductor material when it is subjected to sunlight. This type of electric power generation is considered clean because its production does not result in the emission of pollutant gases, besides, it is a renewable energy, due to the sun's inexhaustible nature. This work presents a study about the implementation of photovoltaic energy in a vertical residential condominium, considering the planning since the beginning of the work, so that the maximum efficiency of the project can be obtained. The objective of this project is to understand the generation of photovoltaic solar energy and the execution of the sizing in residential installations, focusing on sustainability, generating energy in a way that is less aggressive to the environment, thus providing well-being to the residents of these condominiums. As a result, it was possible to verify that with the dimension of the generator in question, it would be possible to supply 12 apartments, totaling a 3-storey residential building.